ANALISIS FAKTOR YANG MEMPENGARUHI TERHADAP PELAYANANMASYARAKAT DI KELURAHAN GUNUNG PANJANG SAMARINDA SEBERANG - Lestari, Mei Tri (PREDIKSI, 2016)
Public Service is any activity undertaken by the government on a number of humanbeings who have any remunerative activity in a collection or entity, and offers asatisfaction even though the results are not tied to a physical product. Influence Approach Attitude (attitude) is the success of the service will be highlydependent on the people involved in it. Either directly or indirectly, the company'simage will be reflected through the type of services that governments provide. thepublic will judge the public service of first impression in touch with the peopleinvolved in the government offices. The influence of the attention (attention) is a service activity, an officer in the publicservice carefully in meeting the wishes of the people so that people are satisfied withthe services provided. Effect of the action (action) is the act of service given by theofficer in meeting the wishes of the people. Basic theory used concepts that support this research is the theory - the theory of theaction, attention and attitude of administrative employees as independent variablesand the public services of the Village as an independent variable with SPSS 19Based on the analysis and discussion, the conclusions of this study are:Variable attitude and attention getting value from SPSS very good results, reachingsig 0000 so that the results concluded that the ministry GunungPanjang villages inSamarinda Seberang get good value in the community. The value of variable actionstill get less value, as perceived by the community action on the service in the longmountain villages is not maximized.